(untitled) (Journal of Face Aesthetics, 2022)
The paper presents views on the face proportions on the basis of selected literature of the last ten years in terms of facial aesthetics. 13 reports from the period of 10 years were analyzed, showing that the proportions of the face are not the most relevant for the assessment of the aesthetics of the face, an individual, original, unique face image is more important.